2010
DOI: 10.2519/jospt.2010.3254
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Low-Intensity Pulsed Ultrasound (LIPUS) Following Tendon Injury Promotes Repair During Granulation but Suppresses Decorin and Biglycan Expression During Remodeling

Abstract: Low-intensity pulsed ultrasound (LIPUS) has been shown to be effective in promoting tendon healing in different animal models of tendon injuries, [3][4][5][9][10][11]14 but the mechanism is not completely understood. In vitro studies on cultured tendon fibroblasts from intact tendons indicated that ultrasound could stimulate collagen production 16 t meTHoDS: In a rat model of patellar tendon donor site injury, a single sonication of LIPUS or mock sonication was delivered to the injured knee of the rats on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Many in vivo studies have demonstrated that LIPUS can be beneficial in improving healing in several other tissue types, including the skin wounds of diabetic and aged mice by increasing fibroblast migration into the wound site (Roper et al, 2015), ischemic heart disease by increasing angiogenesis (Hanawa et al, 2014), tendon repair (Jeremias Junior et al, 2011;Lu et al, 2016) by increasing collagen synthesis (Fu et al, 2010), and muscle repair after injury by increasing myofibre regeneration .…”
Section: Introductionmentioning
confidence: 99%
“…Many in vivo studies have demonstrated that LIPUS can be beneficial in improving healing in several other tissue types, including the skin wounds of diabetic and aged mice by increasing fibroblast migration into the wound site (Roper et al, 2015), ischemic heart disease by increasing angiogenesis (Hanawa et al, 2014), tendon repair (Jeremias Junior et al, 2011;Lu et al, 2016) by increasing collagen synthesis (Fu et al, 2010), and muscle repair after injury by increasing myofibre regeneration .…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Additionally, an examination of treatment time and duration found that introducing LITUS in the earlier stages of healing increased tensile strength and matrix synthesis compared to the later stages of healing. 21,29 In three human studies examining epicondylitis and patellar tendinopathy, tendon pain was significantly decreased in a clinically meaningful way by up to 70% with daily applied continuous LITUS over the course of 6 weeks, 47 although in two of the studies pulsed LITUS produced similar decreases in pain with the control groups. 11,14 …”
Section: Resultsmentioning
confidence: 99%
“…7,14,15 In addition, it has been shown that low-intensity pulsed ultrasound has a positive effect on tendon healing. 14,15,35 Although many results are encouraging, the influence of ultrasound on the structural properties of healing tendons is far from being universally agreed upon. 22 Among parameters that influence treatment effectiveness, particular attention must be given to current intensity.…”
mentioning
confidence: 99%
“…In vitro and in vivo studies have shown that therapeutic ultrasound promotes formation and maturation of healing tissues 26 through increased protein synthesis, 8,27 increased fibroblast proliferation, 6,28 increased growth factor release, 16,30 angiogenesis, 36 and collagen reorganization. 3,14,17 Its most significant benefits occur during the inflammatory, granulation, and proliferative phases of the healing process. 7,14,15 In addition, it has been shown that low-intensity pulsed ultrasound has a positive effect on tendon healing.…”
mentioning
confidence: 99%
See 1 more Smart Citation